Bentazon Determination by Conductometric Titrantion Using Acid Hydrocholoric as Titrant - Silva, J. L. da [UNESP]; Camargo, J. S.; Marchesin, C. M.; Cardoso, C. A. L.; Fiorucci, A. R. (Brazilian Chemical Soc, 2016)
Bentazon is an active principle of post-emergence herbicides used to control weeds in several crops of oilseeds, leguminous and cereals. Commercial formulations of these herbicides are found as concentrated solutions of the bentazon sodium salt. This work proposes a new method for determination of bentazon in commercial formulation of the herbicide based on the conductometric titration of bentazon sodium salt employing hydrochloric acid as titrant. Well-defined titration curves were obtained using the best conditions established for the formation of the reaction product, bentazon acid, employing a temperature of 5.0 degrees C and standby time of the conductivity measurement after addition of the titrant of 90 seconds. The method was applied to determine the bentazon sodium salt in commercial formulation. The results obtained by the proposed method showed agreement with the results obtained in voltammetric and chromatographic methods. The method was also applied in the back-titration with excess sodium hydroxide and the concentration of bentazon, in its acid form, was determined in solid sample obtained by acid extraction process of bentazon in commercial formulation.
Keywords: Bentazone; herbicide; conductometric titration